A Design Strategic to Promoting Social Dimension Through Hawker Experience in Hawker Environment: A Case Study in Bukit Mertajam Old Town, Penang - Lim , Chin Khai; Azlan, Aznida (MAJ - Malaysia Architectural Journal, 2022)
Hawker environment is a casual eating out place where serves various street food. The hawker environment provides an opportunity for people to taste local traditional dishes with a cheap price & meet each other casually (Backhaus, 2020). Consequently, Penang, known as the Pearl of the Orient, is a famous food destination among Malaysians and tourists. Its popularities are based on the existence of hawker culture that reflects the composition and the lifestyle of local people. Penang hawker culture is playing a social role in the communities. However, However, there no previous studies are analyzing the relationship between hawker environment and hawker experience to promote social dimension in communities. Therefore, this study aims to formulate a new design criterion for quality hawker environment in public space and promoting social dimension in Bukit Mertajam old town. Based on qualitative approach, this study involved a content analysis of 10 narratives from Bukit Mertajam local people. The results are expected to identify the hawker experience & hawker spaces that able to embrace the hawker environment to promote social dimension. The study contributes to combine different body of knowledge and contribute design framework for promoting social dimension in public space through hawker environment. Future research can conduct quantitative research to investigate people behavior in hawker environment.